Identification of CIMMYT spring bread wheat germplasm maintaining superior grain yield and quality under heat-stress. (May 2020) - Fleitas, María Constanza; Mondal, Suchismita; Gerard, Guillermo Sebastián; Hernández-Espinosa, Nayeli; Singh, Ravi Prakash; Crossa, José; Guzmán, Carlos
Abstract: Unpredictable temperatures and rainfall associated with climate change are expected to affect wheat ( Triticum aestivum L.) production in various countries. The development of climate-resilient spring wheat cultivars able to maintain grain yield and quality is essential to food security and economic returns. We tested 54 CIMMYT spring bread wheat genotypes, developed and/or released over a span of 50 years, in the field for two years under optimum sowing dates, as well as using two delayed sowing dates to expose crops to medium and severe heat-stress conditions. The grain yield and yield components were severely affected as the heat-stress increased. Two contrasting groups of 10 lines each were identified to determine the effect of heat-stress on bread-making quality. The first set included entries that produced high yields in optimal conditions and maintained higher yields under heat-stress (superior-yielding lines), while the second set included genotypes that did not perform well in the environment with high temperature (inferior-yielding lines). We identified genotypes exhibiting bread-making quality stability, as well as the quality traits that had higher correlation with the loaf volume in the environment without stress and under heat-stress. Of all the quality traits tested, dough extensibility (Alv L ) and grain protein content had a significant influence in heat-stress adaptation. Most of the lines from the superior-yielding group were also able to maintain and even improve quality characteristics under heat-stress and therefore, could be used as parents in breeding to develop high-yielding and stable quality wheat varieties. Graphical abstract: Image 1 Highlights: Grain yield was severely affected as the heat stress increased. Genotypes were considered tolerant and sensitive. Lines from the tolerant group were also able to preserve grain quality.